Synthesis, characterization, and electrochemistry of phosphine-substituted diiron butane-1, 2-dithiolate complexes. Issue 15 (3rd August 2019) - Lin, Hui-Min; Mu, Chao; Li, Ao; Liu, Xu-Feng; Li, Yu-Long; Jiang, Zhong-Qing; Wu, Hong-Ke
Abstract: The reactions of the starting complex, [Fe2 (CO)6 μ -SCH2 CH (CH2 CH3 )S] (1 ), with the phosphine ligands tris(4-methylphenyl)phosphine, diphenyl-2-pyridylphosphine, tris(4-fluorophenyl)phosphine, 2-(diphenylphosphino)benzaldehyde, or benzyldiphenylphosphine in the presence of the decarbonylating agent Me3 NO·2H2 O yielded the corresponding phosphine-substituted diiron butane-1, 2-dithiolate complexes [Fe2 (CO)5 (L) μ -SCH2 CH(CH2 CH3 )S] (L = P(4-C6 H4 CH3 )3, 2 ; Ph2 P(2-C5 H4 N), 3 ; P(4-C6 H4 F)3, 4 ; Ph2 P(2-C6 H4 CHO), 5 ; Ph2 PCH2 Ph, 6 ) in 75%–87% yields. The complexes have been characterized by elemental analysis, IR, 1 H, and 31 P 1 H NMR spectroscopy, as well as by single-crystal X-ray diffraction analysis. Moreover, the electrochemistry of 2 –4 was studied by cyclic voltammetry, suggesting that they can catalyze the reduction of protons to H2 in the presence of HOAc. Graphical Abstract: